"Always Know Where the Gun Is": Service Providers Perceptions of Firearm Access, Violence, and Safety Planning During the COVID-19 Pandemic. Issue 21 (November 2022) - Lynch, Kellie R.; Logan, TK
Given the heightened risk for fatality and known non-fatal harm firearms pose in abusive situations, it is critical to consider the impact of the COVID-19 pandemic on firearm-related abuse and safety planning—particularly considering the surge in firearm sales in 2020. This study documented the impact of the pandemic on firearm access and violence, advice and safety planning surrounding firearms, and firearm-related abuse tactics through the perspective of victim service providers across the US participants included victim service professionals from both rural ( n = 93) and urban/suburban (i.e., non-rural; n = 78) areas who worked with victims of gender-based violence (i.e., intimate partner abuse and dating violence, child abuse, elder abuse, sexual assault, stalking, or human trafficking victims). Results revealed that nearly half of participants reported that abusers threatening to shoot victims or others became more frequent since the start of the pandemic, while nearly 30% reported that homicide involving firearms became more frequent during the pandemic. Further, nearly 40% of participants indicated an increase in firearm sales during pandemic—with higher sales in non-rural versus rural areas. Common themes related to safety planning with firearms included advising the victim to contact the system for help, assessing the location of firearms and/or remove the firearms, and leaving the abuser. The results stress the importance for safety planning around firearms when victims are isolated with an abuser at home and potential impact of abuser firearm access on public safety.